A single-centre Preterm infant Retrospective Analysis of post 6-week Immunisation SideEffects, ‘PRAISE' study, in a busy neonatal unit in the Western Cape, South Africa between 2016-2018 - Petersen, Mishkah (Department of Paediatrics and Child Health, 2024)
Background: Vaccine-Preventable Diseases (VPDs) are a leading cause of the high Underfive Mortality Rate (U5MR). Preterm infants are inherently at higher risk of mortality from VPDs. Studies irrefutably show the benefit of vaccinating preterm infants according to their chronological age with the benefit of timely vaccination outweighing unjustified delays. However, later studies have shown an increased risk of adverse events (AEs) following immunisation (AEFI) in preterm infants. This risk has not been uniformly accepted as statistically significant, but the multiple reports have led to subsequent proposed 48–72-hour cardio-respiratory monitoring recommendations which have not been uniformly adopted and may not be feasible in Low-and-Middle Income Countries (LMICs). Objectives: The main objective of this study is to identify the prevalence of major AEs following 6-week immunisation of preterm infants admitted to a busy neonatal unit in Cape Town over a two-year period. AEFI will be scrutinized to ascertain the timing, clinical severity and possible contributing factors. This study aims to identify any consistent variables or a subset of higher-risk preterm infants to inform a safe and practical in-hospital preterm vaccination and monitoring protocol. Methods: A retrospective audit was conducted on 260 eligible, in-patient, preterm infants receiving the 6-week vaccination as per the South African Expanded Programme on Immunisation (EPI) schedule from 01 March 2016 -31 March 2018 at a busy secondarylevel maternity referral hospital, Mowbray Maternity Hospital (MMH). Results: Two hundred and sixty (260) participants were included in the study, the median gestational age (GA) was 29 weeks, median birth weight 1 078 g and the median age at immunisation 44 days. Thirty-eight (38) out of the 260 participants (14.6%) experienced an AEFI with a median birth GA 28 weeks and median birth weight 988 g. Twenty-nine (29) out of 38 were deemed immunisation-related, since no other cause could be identified, with a prevalence of 11.15%. Majority (89.4%) of AEFI occurred within 24 hours. GA was inversely proportional to the risk of an AEFI. Respiratory support was needed by 73.7% and 97% were screened and treated for sepsis. Conclusion: Established benefit exists in vaccinating preterm infants according to chronological age. However, due cognisance should be paid to the early preterm infant's higher risk of AEFI, 11.15% in our study. Our study supports a clear unit-individualised preterm immunisation protocol with a minimum 24 hours of cardio-respiratory monitoring post vaccination, especially in the very preterm infants <32 weeks GA.